2009 IEEE International Conference on Communications 2009
DOI: 10.1109/icc.2009.5199101
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of H.264 Video Streaming over an IEEE 802.11e EDCA Wireless Testbed

Abstract: Abstract-Although a number of investigations have been conducted using IEEE 802.11e enabled networks to stream class differentiated video, very few reports are available based on a real testbed. In our work, we set up a wireless testbed for H.264 video streaming through assigning the partitioned video packets onto the DCF MAC layer and different access classes of the EDCA MAC layer. We investigate three assignment schemes: 1) DCF is used and all the traffic is treated equally; 2) video traffic is assigned to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…In addition, Haywood, et al [15] have proposed a video streaming over IEEE 802.11e EDCA on real test-bed. The video is streamed for both EDCA and DCF.…”
Section: Cross-layer Optimization For Real-time Video Streamingmentioning
confidence: 97%
“…In addition, Haywood, et al [15] have proposed a video streaming over IEEE 802.11e EDCA on real test-bed. The video is streamed for both EDCA and DCF.…”
Section: Cross-layer Optimization For Real-time Video Streamingmentioning
confidence: 97%
“…This work, which is contemporary with that reported in [12], confirms the advantage of this type of mapping. The authors of [27] also employed priority classification based on data partitioning but tested the results in an indoor wireless testbed with three laptops as receivers. Best-effort TCP traffic was also present.…”
Section: Discussionmentioning
confidence: 99%
“…However, again this paper's primary concern was transmission issues. In a similar vein, in [12] measurements of an IEEE 802.11e data-partitioned scheme indicated that using a single IEEE 802.11e AC was preferable to splitting the H.264 data-partitioned layers across the IEEE 802.11e ACs. However, in the experiments partition B and C packets were assigned to the same IEEE 802.11e AC.…”
Section: Introductionmentioning
confidence: 95%